Preferensi Masyarakat Desa dan Kota Terhadap Perbankan Syariah di Kabupaten Jember - Yuliati, Lilis; Rohmah, Fifi Nur; Sofianti, Septarina Prita Dania (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: This study aims to determine the preferences of rural and urban communities in Jember Regency for Islamic banking. Several factors influence these preferences, including knowledge of Islamic banking and the location of Islamic banking. Research Methods: This research method used a quantitative approach with multiple linear regression analysis. The object of his research includes rural and urban communities in Jember Regency. The sample selection in this study used random sampling of 200 respondents and was carried out randomly. Results: The variable knowledge of Islamic banking in urban and rural communities positively and significantly influences Islamic banking in Jember Regency. Furthermore, the variable location of Islamic banking in rural and urban communities positively influences Islamic banking in Jember Regency. Conclusion: Thus, it is necessary to expand access to Islamic banks to continue increasing the number of offices so that the general public can find information about Islamic banking. This is an excellent opportunity for financial institutions such as Islamic banks to exist and be sustainable.